2016
DOI: 10.1007/s10802-016-0242-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Response during Multisystemic Therapy: Exploring Subgroups and Predictors

Abstract: Multiple studies have shown that Multisystemic Therapy (MST) is, at group level, an effective treatment for adolescents showing serious externalizing problem behavior. The current study expands previous research on MST by, first, examining whether subgroups of participants who respond differently to treatment could be identified. Second, we investigated if the different trajectories of change during MST could be predicted by individual (hostile attributions) and contextual (parental sense of parenting competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Whilst the majority of tertiary prevention strategies are provided in prison settings, as demonstrated in IM these can also be provided in the community. Multi-Systemic Therapy (MST; Henggeler et al 1992) is a home-based intervention for adolescents, aged 12-17 years, that have engaged in offending behavior (Mertens et al 2017). According to MST, deviant behavior is a product of the proximal systems (i.e., family, peer groups, school, and community) that the young person belongs to.…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…Whilst the majority of tertiary prevention strategies are provided in prison settings, as demonstrated in IM these can also be provided in the community. Multi-Systemic Therapy (MST; Henggeler et al 1992) is a home-based intervention for adolescents, aged 12-17 years, that have engaged in offending behavior (Mertens et al 2017). According to MST, deviant behavior is a product of the proximal systems (i.e., family, peer groups, school, and community) that the young person belongs to.…”
Section: Tertiary Preventionmentioning
confidence: 99%
“…MST decreases youth problem behavior including criminal behavior and substance abuse through working directly with families and improving family functioning. However, to our knowledge, except two studies (Halliday-Boykins et al 2004 ; Mertens et al 2017 ), most of the extant studies evaluated the success of MST in reducing serious problem behavior by examining the average changes in the participants. However, the variations across individuals should also be examined to better understand how MST works or for whom.…”
Section: Introductionmentioning
confidence: 99%
“…However, the variations across individuals should also be examined to better understand how MST works or for whom. Halliday-Boykins et al (Halliday-Boykins et al 2004 ), and Mertens et al (Mertens et al 2017 ), on the other hand, examined the trajectories of change in adolescents’ externalizing and/or internalizing behaviors who received MST, and found various subgroups responding differently to treatment. For example, Mertens et al (Mertens et al 2017 ) identified six groups of youth, four of which showed a positive effect of MST with decreases in externalizing behaviors, while two of which displayed poor treatment response by showing either no change or increase in externalizing behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations